Dispersion of carbon nanotubes in aluminum improves radiation resistance. (April 2016) - So, Kang Pyo; Chen, Di; Kushima, Akihiro; Li, Mingda; Kim, Sangtae; Yang, Yang; Wang, Ziqiang; Park, Jong Gil; Lee, Young Hee; Gonzalez, Rafael I.; Kiwi, Miguel; Bringa, Eduardo M.; et al.
Abstract: We can mass-produce metal/carbon nanotube (CNT) composites that show improved radiation tolerance. The 0.5 wt% Al+CNT composite showed improved tensile strength without reduction of tensile ductility before radiation, and reduced void/pore generation and radiation embrittlement at high displacements per atom (DPA). Under helium ion irradiation up to 72 DPA, the 1D carbon nanostructures survive, while sp 2 bonded graphene transforms to sp 3 tetrahedral amorphous carbon. Self-ion (Al) irradiation converts CNTs to a metastable form of Al4 C3, but still as slender 1D nanorods with prolific internal interfaces that catalyze recombination of radiation defects, reducing radiation hardening and porosity generation. The 1D fillers may also form percolating paths of "nano-chimneys" that outgas the accumulated helium and other fission gases, providing an essential solution to the gas accumulation problem. Graphical abstract: Highlights: Dispersion of CNTs showed improved tensile strength without reduction of ductility. CNTs in Al reduced void/pore generation and radiation embrittlement at high DPA. Under He ion irradiation, 1D CNTs survive, while sp 2 bond transform to sp 3 carbon. Formation of metastable 1D Al4 C3 from CNTs still recombine radiation defects. This nanocomposite can help improve bulk properties for nuclear applications.